2020
DOI: 10.30773/pi.2019.0225
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Process-Based Cognitive Training on Memory in the Healthy Elderly and Patients with Mild Cognitive Impairment: A Randomized Controlled Trial

Abstract: Objective This study investigated the effects of process-based cognitive training that targets working memory and cognitive control on memory improvement in healthy elderly individuals and patients with mild cognitive impairment (MCI).Methods Forty healthy subjects and 40 patients with MCI were randomly assigned to either the intervention or control group. The intervention group received 12 sessions of designated cognitive training. The control group did not receive cognitive training. A memory test was admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Memory is a complex and multifaceted cognitive domain that is most commonly affected in cases of MCI (25). Gathering or assimilating new information not only requires the ability to store but also the use of strategies aimed at facilitating the memorization process.…”
Section: Discussionmentioning
confidence: 99%
“…Memory is a complex and multifaceted cognitive domain that is most commonly affected in cases of MCI (25). Gathering or assimilating new information not only requires the ability to store but also the use of strategies aimed at facilitating the memorization process.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that cognitive activity can reduce depressive symptoms in patients with MCI and dementia (Chan et al., 2020; De et al., 2016). One study has shown that cognitive activity can improve the depressive symptoms of patients with MCI and dementia by breaking the vicious circle of negative thinking (Shin et al., 2020). Accordingly, a combination of physical and cognitive activities can maximize the roles of both.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that cognitive training is a potentially effective way to improve EF in older adults with MCI [ 6 , 7 ]. Two recent studies suggest that process-based cognitive training focusing primarily EF is particularly effective among the various training approaches [ 8 , 9 ]. Process-based cognitive training refers to the repetitive practice of computerized and/or manual cognitive tasks without explicit strategies [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two recent studies suggest that process-based cognitive training focusing primarily EF is particularly effective among the various training approaches [ 8 , 9 ]. Process-based cognitive training refers to the repetitive practice of computerized and/or manual cognitive tasks without explicit strategies [ 8 , 9 ]. Several studies provided evidence to support the effectiveness of process-based cognitive training in enhancing EF among both younger and older individuals [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%